Speaking in Worlds of Adventure: Tabletop Roleplaying Games within the EFL Classroom - Fabio Adrian Torres-Rodriguez; Liliana Martínez-Granada (Asociación Colombiana de Profesores de Ingles, 2022)
Fostering spoken communication in a foreign language classroom is not an easy task. With that in mind, this paper explores a proposal to motivate students' L2 oral communication through the practice of narrative games called tabletop roleplaying games adapted as task-based activities. It implied an action research process in which the teacher-researcher with his students reflected and intervened on the identified problematic situation: Lack of oral communication in L2. In that sense, it started with a diagnostic test that showed the current state of verbal communication in L2 in a Colombian rural public school. Next, the teacher-researcher chose to appeal to the gamification of the classroom along with the adoption of a task-based framework to activity design aiming to improve students' motivation to take the risk of communicating in L2. The teacher-researcher applied sets of activities that progressed from traditional role-play to a tabletop roleplaying game. In accordance, video recordings, narratives, artifacts collections, and semi-structured interviews were essential to collect data. Afterward, the teacher-researcher analyzed the data with an emic approach to identify patterns in the information that uncovered the categories and subcategories of information. Consequently, the teacher-researcher concluded that the students feel better motivated using L2 if the learning environment offers opportunities for social interaction, collaborative work, and scaffolding in task-based exercises embedded in a fictional world game.